1998
DOI: 10.1002/pro.5560070225
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis and structural characterization of the RGD‐protein decorsin: A potent inhibitor of platelet aggregation

Abstract: Decorsin is a 39-residue RGD-protein crosslinked by three disulfide bridges isolated from the leech Mucrobdellu decoru belonging to the family of GPIIb-IIIa antagonists and acting as a potent inhibitor of platelet aggregation. Here we report the solid-phase synthesis of decorsin using the Fmoc strategy. The crude polypeptide was purified by reverse-phase HPLC in its reduced form and allowed to refold in the presence of glutathione. The homogeneity of the synthetic oxidized decorsin was established by reverse-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 82 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…After obtaining a racemization‐minimized crude linear protoxin II, crude peptide was then air oxidized to form disulfide bridges. When disulfides are in the Cys1–Cys4, Cys2–Cys5 and Cys3–Cys6 bridging pattern, air oxidation is a robust method to form these disulfide bridges with high yield. Steiner and Bulaj reported a summary of oxidative folding conditions in which it was observed that a pH of 6–8 was optimal and the ratio between reduced and oxidized glutathione does not significantly affect the efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After obtaining a racemization‐minimized crude linear protoxin II, crude peptide was then air oxidized to form disulfide bridges. When disulfides are in the Cys1–Cys4, Cys2–Cys5 and Cys3–Cys6 bridging pattern, air oxidation is a robust method to form these disulfide bridges with high yield. Steiner and Bulaj reported a summary of oxidative folding conditions in which it was observed that a pH of 6–8 was optimal and the ratio between reduced and oxidized glutathione does not significantly affect the efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Cysteine residues are known to racemize during coupling in Fmoc solid phase peptide synthesis (Fmoc‐SPPS) , and this problematic issue is even more complex when synthesizing toxins from venomous animals because of the complex arrangement of multiple disulfide bonds. There are numerous reports on the Fmoc‐SPPS of naturally occurring inhibitory cystine knot peptides such as protoxin II , but interestingly, none of these previous publications mention the extent (or lack thereof) of cysteine racemization and thus create possible ambiguity regarding the chiral purity of the reported peptides. Given that each cysteine may racemize (5–50%) during the synthetic process, the desired crude linear toxin may only comprise a small fraction of the crude product, making it difficult to isolate and subsequently purify.…”
Section: Introductionmentioning
confidence: 99%
“…The stabilizing role of disulfide bridges in proteins is well illustrated in the structural studies of decorsin, a 39-residue protein isolated from the blood-sucking leech, Macobdella decora, which has the powerful ability to prevent blood clot formation . Decorsin has been intensively studied as a potential therapeutic agent or a model for other inhibitors of platelet aggregation.…”
mentioning
confidence: 99%